Lebanese leaders - Rowayheb, Marwan (2014)
This article argues that the lack of improvement regarding the empowerment of Lebanese youth and women in political movements, political parties, and the public and governmental sectors should be attributed not only to cultural, social, and religious factors, but, as argued in many cases, to the political considerations of the leaders of many of these political movements and political parties. This is revealed by an examination of the cases of Samir Geagea, the leader of the Lebanese Forces, and Michel Aoun, the leader of the Free Patriotic Movement. This article argues that Aoun and Geagea had the power and influence to assist the women and youth of their movements to become more politically empowered, as well as within the public and governmental sectors. However, neither made any serious attempt in that direction. Both have been trying to become the unchallenged sole leader of the Lebanese Christians by relying on political alliances and the internal management of his respective political movement. Although Aoun and Geagea differ in the way that they manage their political alliances, they manage their movements in a similar fashion that impedes the improvement of women and youths’ political participation.